2018
DOI: 10.1007/s00264-018-3987-7
|View full text |Cite
|
Sign up to set email alerts
|

Cementless total hip arthroplasty for osteonecrosis and osteoarthritis produce similar results at ten years follow-up when matched for age and gender

Abstract: The functional outcomes, implant survival, and rate of complications for cementless THAs are comparable at a mean follow-up of ten years for ONFH and OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…These unsatisfactory outcomes can be attributed to the usual patient's young age, but also the associated diseases that are the cause of osteonecrosis as corticosteroids and sickle cell disease. Interestingly, recent reports [30,31] seem to demonstrate that the risk of revision of arthroplasty in osteonecrosis is not as high as suspected at least during the first 10 years of follow-up. Furthermore, lower rates of revision are noted with systemic lupus erythematosus [32] where a lower level of activity of the patient is probably observed.…”
Section: Total Hip Arthroplasty and Osteonecrosismentioning
confidence: 99%
“…These unsatisfactory outcomes can be attributed to the usual patient's young age, but also the associated diseases that are the cause of osteonecrosis as corticosteroids and sickle cell disease. Interestingly, recent reports [30,31] seem to demonstrate that the risk of revision of arthroplasty in osteonecrosis is not as high as suspected at least during the first 10 years of follow-up. Furthermore, lower rates of revision are noted with systemic lupus erythematosus [32] where a lower level of activity of the patient is probably observed.…”
Section: Total Hip Arthroplasty and Osteonecrosismentioning
confidence: 99%
“…Previous reports have demonstrated that both mental state and hip-joint function are similarly impaired in patients with ONFH with progressing collapse of the femoral head [1,2]. Chen et al reported a signi cantly higher prevalence of depression in patients with ONFH than in those with OA [20], and in another study, patients with ONFH had signi cantly lower mental scores after THA than patients with OA [9].…”
Section: Discussionmentioning
confidence: 94%
“…Considering recently reported long-term outcomes [9,24], We believe that THA should be the rst choice for treatment of ONFH. However, THA is not recommended for young people due to the risk for multiple revision surgeries in the future; surgical strategies should be carefully selected since performing the appropriate joint-preserving surgery can provide long-term functional outcomes that are equivalent to those provided by THA [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The terminal course of ONFH is femoral head collapse, articular cartilage degeneration, and subsequent late-stage osteoarthritis when no timely treatment initiated [3, 4]. Total hip arthroplasty (THA) can resolve the condition with definite success and long-term satisfactory outcomes [5]. However, regardless of improvements in joint prosthesis design, instruments, and surgical techniques, THA is unlikely to be endured for the rest of the life of the acceptors, especially for young individuals.…”
Section: Introductionmentioning
confidence: 99%